Diversidad florística, concentración de biomasa aérea y carbono (c) en un bosque siempre verde tierras bajas de 300 a 400 msnm., en la Amazonía Ecuatoriana - Estrella Caicedo, Luis Amable (2016)
The aim of this research was to evaluate the floristic diversity, aboveground biomass and carbon sequestration (C) in an evergreen forest lowland 300-400 meters above sea level located in the province of Napo, where 20 temporary plots of 625 m2 were implemented. The results show an average concentration of 249.7 Mega grams of Carbon per hectare (Mg/ha) in this type of forests in this area. The outcomes also display a high diversity index according to Shannon index of 3,711 and Simpson index of 0.93. The ten botanical families that contribute most to carbon storage were: Myristicacea, Arecaceae, Lauraceae, Morecaeae, Malvaceae, Melatomataceae, Lecythidaceae, Combretaceae, Urticaceae, Fabacea in descending order of importance, while the ten species most sequester Carbon were: Iriartea deltoid, Ocotea sp., Tessmannianthus sp., Grias neuberthii, Terminalia sp., Otoba glycicarpa, Virola duckei, Apeiba membranaceae and Ruizodendron ovale. The paper concludes with a recommendation to decision makers consider these results in future reforestation projects with commercial, climate change mitigation or conservation of species purposes.